PENERAPAN ARCS PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL STAD DAN NHT DI SMP NEGERI 3 AMPELGADING MALANG - Ummi Laila Nurjannah (Qalam : Jurnal Ilmu Kependidikan, 2018)
The purpose of the study was to describe: the application of the ARCS model of learning mathematics using STAD and NHT in SMP Negeri 3 Malang Ampelgading, activities of teachers and learning activities of students during the learning process, as well as student learning outcomes and student motivation. The approach taken in this study is a qualitative and quantitative approach. The experiment was conducted in the first semester of 2013-2014 academic year on 28 October to 16 November 2013 in which the application of the ARCS model of learning using STAD and NHT to see the activities of the teacher and student learning activities as processes of learning, student learning outcomes are seen from individual tasks and daily test as well as the student's motivation to learn the subject while in the eighth grade students of SMP Negeri 3 Malang Ampelgading as objects. Instrument used is the observation sheet to see the activities of teachers and students’ learning activities, individual assignments and daily test to look at student learning outcomes and questionnaire to see the students' motivation . The results showed that: 1) the application of the ARCS model of learning mathematics using STAD and NHT in SMP Negeri 3 Malang Ampelgading accomplished in accordance with the RPP planned despite having some problems at the beginning of the meeting, 2) the activities of teachers and students' learning activities always have improvement in every meeting, in which the first meeting activities better teacher in class VIII-A, the second meeting better in class VIII-B and the third meeting has the same score, while for student activities, class VIII-B is always more better than VIII-A, 3) there is no difference in learning outcomes between students of class VIII-A that is taught using STAD and the ARCS model of class VIII-B are taught using a model ARCS and NHT, 4) there is no difference between the learning motivation of class VIII-A students who are taught using STAD and the ARCS model of class VIII-B are taught using a model ARCS and NHT .